Controlled synthesis of nanoplate, nanoprism and nanopyramid-shaped CdSe decorated on porous TiO2 photocatalysts for visible-light-driven hydrogen evolution. Issue 11 (1st August 2018) - Yang, Mengke; Qian, Yongteng; Du, Jimin; Yuan, Sijie; Wang, Sijia; Zhu, Xinrui; Lin, Xialing; Li, Kaidi; Li, Sujuan; Kang, Dae Joon
Abstract: Herein, we report a successful synthesis of porous TiO2 monoliths decorated with unique nanoplate, nanoprism, and nanopyramid-shaped CdSe particles through a mild selenylation of CdO embedded inside porous TiO2 monoliths via a hydrothermal method in a very controlled manner. Compared with pure TiO2, as-synthesized CdSe/TiO2 photocatalyst not only enhances light absorption but also leads to a highly efficient charge-carrier separation. Particularly, the nanoplate-shaped 7% CdSe/TiO2 photocatalyst (molar percentages of CdSe to TiO2 is 7:100) exhibits an exceptional hydrogen evolution rate up to 3650 μmol h −1 g −1 without resorting to any noble-metal co-catalysts under visible-light irradiation owing to synergistic effects envisaged by a rational material design. Our results may provide a useful strategy to develop a highly-efficient visible-light-driven hydrogen production system via water splitting.